The Use Of Blended Learning Model In The Application Of Audacity Applications In History Subjects At Sma Labschool Untad Palu - Hasan, Hasan; Abdul Latief, Juraid; Suyuti, Suyuti (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by the low ability of teachers in designing online-based learning during the pandemic, and teachers do not yet have the competence to integrate the Blended Learning learning model packaged in the Audacity Application with the subject matter of History at SMA Labschool. This research has an urgency to be carried out, so that through this research will give birth to new innovations in combining the blended learning model with the Audacity application in the history learning process by raising local historical values ​​as a lesson package in high school. This research is oriented towards new breakthroughs in facing the industrial revolution era. In this study, the problems are 1. How to apply the blended learning model using the Audacity Application in History lessons at SMA Labschool and 2. How to improve student learning outcomes by applying the Blended Learning Model using the Audacity Application to History Lessons in Senior High Schools in Central Sulawesi. The purpose of this study is oriented to determine the pattern of application of the blended learning learning model using the Audacity Application in history lessons at Senior High Schools in Central Sulawesi. Thus, Labschool SMA teachers by applying the blended learning model combined with the Audacity Application will facilitate the learning process. This research is a qualitative research which is studied using a blended learning model approach as the basis in the learning process combined with Audacity technology as a medium in delivering history subject matter in high schools throughout Central Sulawesi. The application of the blended learning learning model which in principle will be one of the solutions and breakthroughs to overcome the difficulties of the learning process at SMA Labschool. Thus, this research process will make it easier for teachers to transfer knowledge to students as objects in the learning process at SMA Labschool. This research is also a novelty that was carried out as a breakthrough in the history learning process at SMA Labschool.